Analysis of the Role of Factors that Influence Brand Loyalty to Food Influencers as Human Brands in Indonesia - Hanif, Fikri (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2024)
This research analyzes the factors that influence brand loyalty towards food influencers, with a particular focus on the impact of interactivity, authenticity, emotional attachment, brand trust, customer engagement, and involvement. A quantitative approach was adopted, utilizing Structural Equation Modeling-Partial Least Squares (SEM-PLS) to analyze data from 215 followers in Indonesia. The SEM-PLS technique allowed for an assessment of both the direct and indirect relationships among the variables impacting loyalty to a human brand. The findings indicate that several factors, including interactivity, brand trust, customer engagement, and involvement, significantly shape brand loyalty. Interactivity is critical to increasing authenticity and emotional engagement, which then strengthens brand trust. This established trust, alongside emotional attachment, drives deeper customer engagement. Engagement plays a mediating role, enhancing the relationship between followers and the brand, resulting in greater brand loyalty. Based on the insights gleaned, influencers are advised to prioritize interactive and authentic communication with their audience, fostering trust and an emotional bond. Consequently, influencers must create content that resonates with their followers to maintain their interest and loyalty over time. This approach reinforces the value of building lasting relationships with an audience in the dynamic sphere of influencer marketing.